ROH KUDUS DAN MISI: Mengungkap Peran Pribadi Ketiga Allah Tritunggal dalam Misi Serta Signifikansi Praktisnya Bagi Gereja Masa Kini - Setiawan, David Eko; Isharjono, Anton (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2022)
This study aims to uncover the role of the Holy Spirit in the mission of the church, with a focus on analyzing the writings of the Synoptic Gospels and the Book of Acts. The research also identifies the practical significance of the Holy Spirit's role for the contemporary mission of the church. The method of library research is utilized to gather data from various relevant literature sources. The findings of the study indicate that the Holy Spirit plays a crucial role in the presence and ministry of Jesus in the world. Furthermore, the Holy Spirit empowers disciples to become effective witnesses of Christ. These findings have practical implications that are relevant to the church today. The church is expected to consistently honor the person of the Holy Spirit as the driving force behind the mission, to submit to Him in the task of mission, and to acknowledge His authority in carrying out the work of God's mission in the world. This research provides a strong theological foundation and practical guidance for the church to fulfill its mission with the power and wisdom of the Holy Spirit.